Diagnostic Accuracy of MRCP for Detecting Choledocholithiasis in Patients with Obstructive Jaundice Keeping ERCP as Gold Standard: MRCP for Detecting Choledocholithiasis in Obstructive Jaundice: Keeping ERCP - Naseem, Kamran; Nisar, Sarah; Mumtaz, Fariha (Pakistan Journal of Health Sciences, 2025)
Choledocholithiasis is a common cause of obstructive jaundice and may lead to serious complications if diagnosis or treatment is delayed. While ERCP is the gold standard for diagnosis and therapy, its invasive nature carries risks. MRCP offers a non-invasive alternative, but its accuracy may be influenced by clinical and technical factors. Objectives: To evaluate the diagnostic accuracy of MRCP in detecting choledocholithiasis using ERCP as the reference standard, and to assess the impact of stone size, location, number, and MRCP–ERCP interval. Methods: This analytical cross-sectional diagnostic accuracy study was conducted in the Department of Radiology, Bahawal Victoria Hospital, Bahawalpur (March 13, 2023, to March 12, 2024). A total of 271 patients with suspected choledocholithiasis underwent both MRCP and ERCP. Sensitivity, specificity, predictive values, overall accuracy, and Cohen’s kappa were calculated with subgroup analyses by stone size, location, number, and MRCP–ERCP interval. Results: MRCP showed a sensitivity of 88.9% (95% CI: 83.5–92.7%), specificity of 67.0% (95% CI: 56.9–75.8%), PPV of 84.2% (95% CI: 78.4–88.7%), NPV of 75.3% (95% CI: 64.9–83.4%) and an overall accuracy of 81.5% (95% CI: 76.5–85.7%). Agreement with ERCP was moderate (Cohen’s kappa = 0.55). Diagnostic performance was highest for stones measuring 5–10 mm, distally located stones, and when ERCP was performed within 3 days of MRCP. Conclusions: MRCP demonstrates good diagnostic accuracy and moderate agreement with ERCP, particularly for medium-sized distal stones and when ERCP is not delayed.